2019
DOI: 10.3389/fnhum.2019.00369
|View full text |Cite
|
Sign up to set email alerts
|

Gender- and Age-Specific Differences in Resting-State Functional Connectivity of the Central Autonomic Network in Adulthood

Abstract: Previous functional imaging studies have identified the role of central autonomic network (CAN) in autonomic regulation during various tasks. However, its variability with respect to gender and age, particularly in the resting state, remains poorly understood. Therefore, in this study we systematically investigated gender- and age-related differences in the resting-state functional connectivity (rsFC) seeded from core regions of this network, namely posterior mid-cingulate gyrus (pMCC), left amygdala, right an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…There are no uniform standards of age boundaries for the division of young, middle and old adults. Previous studies applied different age boundaries due to various datasets and research methods and we select the same age boundaries as in previous studies (Sie et al, 2019 ) due to the use of the same dataset. The dataset included 494 healthy volunteers (187 males and 307 females, aged 19–80) in which 2 participants did not complete the resting-state scanning and 31 participants were excluded due to excessive head motion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no uniform standards of age boundaries for the division of young, middle and old adults. Previous studies applied different age boundaries due to various datasets and research methods and we select the same age boundaries as in previous studies (Sie et al, 2019 ) due to the use of the same dataset. The dataset included 494 healthy volunteers (187 males and 307 females, aged 19–80) in which 2 participants did not complete the resting-state scanning and 31 participants were excluded due to excessive head motion.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset included 494 healthy volunteers (187 males and 307 females, aged 19–80) in which 2 participants did not complete the resting-state scanning and 31 participants were excluded due to excessive head motion. The remaining 461 participants were grouped into Young (19–34), Middle (35–59), and Old (60–80) age groups (Sie et al, 2019 ), with 170, 183, and 108 subjects in each group. Figure 1 showed the distribution of males and females of the groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Voxel-wise TBSS with permutation tests on the final FA skeleton was conducted to identify differences in white matter integrity between individuals with MDD and the control group using the FSL/RANDOMISE tool (5,000 permutations), controlling for age, gender, and age × gender interaction. We included these covariates in our analyses due to the large age range of our participants and because previous studies suggested that age and gender should be controlled for in functional connectivity studies ( Sie et al, 2019 , C. Zhang et al, 2016 ).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Despite the well-documented human preponderance of females afflicted by mood disorders (104,105), the majority of identified studies utilized males only, or did not report the sex of experimental animals. Importantly, out of the 17 studies that included both male and female animals, one study used males for inhibition and females for activation (106), another used females only for tracing studies (107), and a third used males for optogenetic and females for chemogenetic manipulation (108).…”
Section: Sex As a Biological Variablementioning
confidence: 99%